Fine Mapping of a Deafness Mutation hml on Mouse Chromosome 10 - Zheng, Qing Yin (2004)
OBJECTIVE: to map a mouse deafness gene, identify the underlying mutation and develop a mouse model for human deafness. METHODS: genetic linkage cross and genome scan were used to map a novel mutation named hypoplasia of the membranous labyrinth (hml), which causes hearing loss in mutant mice. RESULTS: 1. hml was mapped on mouse Chr 10 (~43 cM from the centromere) suggests that the homologous human gene is on 12q22-q24, which was defined on the basis of known mouse-human homologies (OMIM, 2004). 2. This study has generated 25 polymorphic microsatellite markers, placed 3 known human genes in the correct order in a high-resolution mouse map and narrowed the hml candidate gene region to a 500kb area.